(untitled) (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
The purpose of this study is to describe tutoring in elementary schools: a description of practice from the perspective of a fourth-grade teacher at SD Negeri 3 Lawahing, based on interviews with an experienced teacher. The main focus of the discussion includes the implementation, objectives, methods, challenges, and evaluation of the tutoring process. Tutoring is seen as an essential part of guidance and counseling services aimed at helping students overcome learning difficulties and improving their academic abilities